2003
DOI: 10.1046/j.1354-523x.2003.00974.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of epithelial cell proliferation between the odontogenic keratocyst, orthokeratinized odontogenic cyst, dentigerous cyst, and ameloblastoma

Abstract: These findings support previous studies that the proliferation indices are useful in predicting the different biological behavior of the odontogenic lesions and the OKC should be regarded as a benign tumor rather than simply an odontogenic cyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
72
1
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 15 publications
7
72
1
9
Order By: Relevance
“…This is in accordance with previous reports (10,11). In contrast, studies have also demonstrated a higher cell proliferation in AM in relation to KOT (7)(8). All these authors used different methods to evaluate PI.…”
Section: Discussioncontrasting
confidence: 33%
See 2 more Smart Citations
“…This is in accordance with previous reports (10,11). In contrast, studies have also demonstrated a higher cell proliferation in AM in relation to KOT (7)(8). All these authors used different methods to evaluate PI.…”
Section: Discussioncontrasting
confidence: 33%
“…Since KOT had been classified as an odontogenic cyst, several authors have compared cell proliferation between KOT and odontogenic cysts (8,12,13). Although several authors have assessed cell proliferation and apoptosis in the odontogenic epithelium in AM and in the epithelial lining in KOT (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), few studies have compared cell proliferation between these tumors (7,8,11) and no previous study has simultaneously evaluated cell proliferation and apoptotic indexes in AM and KOT, comparing both lesions. Therefore, this is the first study assessing comparatively cell proliferation and apoptosis indexes in AM and KOT, although tissue cell population is controlled by a balance among these processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prominent palisaded and hyperchromatic nuclei in the basal cell layer are not seen in OOC. Many studies have also found different histochemical and immunohistochemical features in OOC from OKC, including significant differences in keratin profiles in the cyst lining epithelium [10], in collagen fibers, fibronectin, or numbers of myofibroblasts in the cyst wall [11][12][13][14], in expression of podoplanin [15], Ki-67, p63 [3], TGF-a, P53 [16], bcl-2 [17], KAI-1 [18], cell proliferating marker IPO-38 [19], calretinin [20], EMA, CEA, and involucrin [21]. These findings lead to the current concept that OOC is a different pathological entity from OKC.…”
Section: Discussionmentioning
confidence: 99%
“…The average number of cells positive for Ki-67 in KOTs, DCs and PFs in this study was in line with values reported in the literature. KOTs presented the greatest proliferation rate among the three groups, with Ki-67 immunolabeling found mainly in the suprabasal layer, suggesting an altered cell cycle and indicating the presence of a suprabasal proliferative compartment [7,22,[30][31][32][33][34]. In DCs, the basal layer was found to be the proliferative compartment [34,35].…”
Section: Discussionmentioning
confidence: 99%